Taxonomic study of the leafhopper genus Anufrievia Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini) from China, with descriptions of two new species - Lin, Shuanghu; Zhang, Yalin (Zootaxa, 2021)
The genus Anufrievia Dworakowska is reviewed with two new species from China: A. anchoroides sp. nov., and A. drepanoides sp. nov.. Detailed morphological descriptions and illustrations of these two new species and a key to all known species (males) from China are provided.